2019
DOI: 10.1016/j.ijrobp.2019.06.2533
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Reduces Intestinal Radiotoxicity, Enabling Dose-Escalated Radiation Therapy for Pancreatic Cancer

Abstract: Completing my PhD thesis project has required the support of a small army composed of mentors, colleagues, friends and family. First and foremost, I'd like to thank both the Taniguchi and Piwnica-Worms' labs for always being there to teach me, help with experiments, edit my writing, and give feedback on oral presentations. Both my mentors; Helen Piwnica-Worms and Cullen Taniguchi were paramount in my growth as a scientist and taught me a deep love and respect for science that I will carry with me throughout my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 115 publications
0
18
0
Order By: Relevance
“…Finally, diet has been implicated in affecting many diseases including heart disease and cancer. A preclinical study revealed fasting reduced intestinal radiotoxicity using C57BL/6J mice, assessed by fasting improved intestinal stem cell regeneration and improved survival to lethal doses of abdominal RT [199]. Musa and Shabeeb reported natural products may have a potential for protection against RIHD, reviewing products such as hesperidin, curcumin, melatonin, zingerone, and Shen-Mai San (SMS), where SMS is examined in a clinical trial for cancer patients receiving chemotherapy or RT (NCT01580358) [200].…”
Section: Influence Of Environmental Factors On Radiation Therapymentioning
confidence: 99%
“…Finally, diet has been implicated in affecting many diseases including heart disease and cancer. A preclinical study revealed fasting reduced intestinal radiotoxicity using C57BL/6J mice, assessed by fasting improved intestinal stem cell regeneration and improved survival to lethal doses of abdominal RT [199]. Musa and Shabeeb reported natural products may have a potential for protection against RIHD, reviewing products such as hesperidin, curcumin, melatonin, zingerone, and Shen-Mai San (SMS), where SMS is examined in a clinical trial for cancer patients receiving chemotherapy or RT (NCT01580358) [200].…”
Section: Influence Of Environmental Factors On Radiation Therapymentioning
confidence: 99%
“…A more recent study by Li and co-workers (48) investigated short fasting periods in mice (12,48, and 72 h with eight mice per group) before radiation, which showed a survival rate of 0, 12.5, and 50%, respectively, in comparison to 0% survival in the control group following 7.5 Gy of γ-rays significance not reported. Additionally, Bonilla et al (38) reported a survival rate of 100% at day 30 in the fasted intervention group and a 0% survival rate in the non-fasted control group (significance not reported).…”
Section: Fastingmentioning
confidence: 95%
“…Cappelli et al (36), reported only raw data from which to determine mean time of survival after exposure and its standard deviation. Yoshida et al (37) and Bonilla et al (38) reported standard error that was converted to standard deviation via:…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
See 2 more Smart Citations